Toward conceptualizing "place immersion" as a spatial neuropsychosocial phenomenon: A multidisciplinary meta-review and -synthesis. (June 2022) - Buttazzoni, Adrian; Ellard, Colin; Sadiora, Sukhmani; Minaker, Leia
Abstract: Scholarship examining diverse relationships between place and human experience continues to be of great interest given that these interactions impact human development, functioning, and health. While many concepts have been developed to capture and quantify the impacts of place-based experiences in recent years, no concept has yet been proposed that outlines the potential experience of immersion in place. This meta-synthesis outlines such a notion through offering a multidisciplinary conceptualization of "place immersion" as a spatially-based neuropsychosocial phenomenon. Place immersion is organized into three domains that contribute to an experience of immersion in place: neuro-spatial (i.e., relevant embodied precognitive processes involved in analyzing and responses to the features of a place), psycho-spatial (i.e., relevant embodied cognition processes involved in the analyzing of and responses to the features of a place), and socio-spatial (i.e., the culturally-, linguistically-, and socially-mediated meanings that are enacted by an individual in a particular place). A composite definition of the concept is offered, and potential research contributions and opportunities for place immersion are also discussed. Highlights: A meta-synthesis containing 73 titles was used to conceptualize 'place immersion'. Place immersion offers a new concept for studying person-place interactions. Future work should examine the concept as a unique experience with multiple methods. Future research could also reorient conceptions of built environment, place uses. Urban designers can use place immersion ideas to better design pedestrian spaces.